Intention to Use Voluntary Counseling and Testing Services among College Students - Kusumaningrum, Tanjung Anitasari Indah; Pratiwi, Handini (Jurnal Promosi Kesehatan Indonesia, 2022)
Background: HIV is a health problem of global concern. A large number of HIV cases in Surakarta is due to various factors such as the characteristics of adolescents, knowledge, attitudes, and beliefs to reduce HIV prevention through the use of VCT services. This study aims to analyze the relationship between age, gender, type of study program, information exposure, organizational participation, knowledge, attitudes, and beliefs in using VCT to use Voluntary Counseling and Testing (VCT) services for college students. Method: This research was a quantitative study with a cross-sectional approach. The study population was all students at one university in Surakarta in the 2016-2017 class as many as 12,457 students, while the research sample was 500 students who were taken using a proportional random sampling technique. Data analysis using chi-square test and logistic regression.  Results: The results of the multivariate analysis showed that students' knowledge of HIV / AIDS and VCT affected the intention to use VCT services with an OR = 1.776 (CI = 1.170-2.695). The bivariate test results showed that there was a relationship between information exposure (p-value = 0.001), knowledge (p-value = 0.007), attitude (p-value = 0.006) and belief (p-value = 0.013) with the intention to use VCT services. Meanwhile, there was no relationship between age (p-value = 0.118), gender (p-value = 0.579), type of study program (p-value = 1,000), organizational participation (p-value = 0.352) with the intention of using VCT services. Students' knowledge of HIV / AIDS and VCT was the most dominant VCT intention. Therefore, providing information about VCT to students is necessary to increase students' knowledge and confidence in using VCT services.